2021
DOI: 10.3390/pathogens10101342
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Modified Live Virus Vaccine against Porcine Reproductive and Respiratory Syndrome Virus 1 (PRRSV-1) Administered to 1-Day-Old Piglets in Front of Heterologous PRRSV-1 Challenge

Abstract: PRRSV is one of the most important viruses in the global swine industry and is often controlled by the use of modified live virus (MLV) vaccines. This study assessed the impact of a PRRSV-1 MLV vaccine applied to 1-day-old piglets challenged on day 28 of life with a PRRSV-1 field isolate (AUT15-33). Twenty-one piglets were vaccinated within 24 h of birth (T02), whereas 20 piglets were left unvaccinated (T01). Necropsy was performed two weeks post-challenge. Comparing the two groups, T02 piglets showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(68 reference statements)
0
10
1
1
Order By: Relevance
“…An in-depth genetic and phenotypic characterization of emerging PRRSV isolates is also pivotal for the control and update of diagnostic methods, the monitoring of vaccine efficacy against new isolates, and also potential changes in virus pathogenicity and virulence. In general, the virulence of different PRRSV isolates was mainly evaluated for respiratory disease in young pigs ( 6 , 13 , 26 , 36 , 54 , 55 ). Additionally, challenge experiments investigating the mechanism of PRRSV-induced reproductive failure were predominately performed with PRRSV-2 ( 41 , 56 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth genetic and phenotypic characterization of emerging PRRSV isolates is also pivotal for the control and update of diagnostic methods, the monitoring of vaccine efficacy against new isolates, and also potential changes in virus pathogenicity and virulence. In general, the virulence of different PRRSV isolates was mainly evaluated for respiratory disease in young pigs ( 6 , 13 , 26 , 36 , 54 , 55 ). Additionally, challenge experiments investigating the mechanism of PRRSV-induced reproductive failure were predominately performed with PRRSV-2 ( 41 , 56 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…For our study, we used a licensed PRRSV-1 MLV for vaccination and challenged with the heterologous PRRSV-1 strain AUT15-33. This PRRSV isolate has been shown to be highly virulent in experimental infection studies with growing pigs and pregnant sows (Kreutzmann et al 2021 , 2022 ; Dürlinger et al 2022 ). In our study, we observed viral loads in the serum of around 8 log 10 genome copies/mL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the MDA, the less responsive nature of adaptive immune cells in young pigs [ 81 ] will provide a further barrier for PRRSV vaccines to generate robust immunity. That said, recent studies that evaluated the administration of a PRRSV MLV vaccine at 1-day of age showed promising results to overcome MDA and decrease viremia, viral shedding, and lung lesions [ 82 , 83 , 84 , 85 ]. These studies might provide a solution for the challenge to not only protect sows from reproductive issues but also young piglets from respiratory disease at a time of elevated stress as well as potentially exposure to high loads of PRRSV.…”
Section: The Problem Of Prrsvmentioning
confidence: 99%
“…If upon transfer to nursery phase, pigs are vaccinated and also are exposed to circulating strains, then it is unlikely maternal PRRSV vaccines will provide protective immunity to nursery-age pigs. Vaccination of newborn piglets [ 83 , 84 , 85 ] appears to be a strategy to overcome concurrent nursery vaccination and exposure; however, the vaccine’s effect must overcome MDA, the piglet’s immature immune system, and the 28 days or more [ 67 ] required for a maximal immune response. In the above studies, challenge occurred at 9 or 18 weeks after vaccination.…”
Section: Plotkin’s Principles Of Correlates Of Protection Applied To ...mentioning
confidence: 99%